التحول الرقمي و دوره في تحسين أداء المؤسسة _ دراسة حالة مؤسسة برندث للأجهزة الكهرومنزلية - خنطيط خديجة (جامعة الوادي University of Eloued, 2024)
This study aimed to know the role of digital transformation in improving the performance of the organization through its dimensions (digital strategy, technological techniques, organizational culture), and to achieve the objectives of the study, the questionnaire was used as a tool to collect data and information from the study sample estimated at 50 frames from Brandt, and 37 questionnaires were retrieved and analyzed, and after statistical treatment the study concluded that the dimensions of digital transformation have a role in improving the performance of Brandt, as there is a strong link between the various dimensions of digital transformation and the performance of the organization, so the success of digital transformation requires integration between its dimensions where we find organizational culture driving the process of digital transformation
Digital transformation and its role in improving organizational performance - case study of Brandt Company
Keywords: تحول رقمي; إستراتجية رقمية; تقنيات تكنولوجية; ثقافة تنظيمية; أداء مؤسسة; Digital transformation; digital strategy; organizational culture; Digital transformation; digital strategy